Effect of low‐level roadway tunneling on gas drainage for underlying coal seam mining: Numerical analysis and field application. Issue 4 (13th May 2021) - Xu, Chao; Sun, Haoshi; Wang, Kai; Qin, Liangliang; Guo, Chaofei; Wen, Zhijie
Abstract: Coalbed methane (CBM), which is extremely rich in deep coal reserves in China, is not only the material cause of gas explosion and coal‐gas outburst disasters but also a clean and environmentally friendly energy source. Gas drainage must be carried out during deep coal mining to avoid gas accidents while obtaining clean energy. The low‐level roadway is an effective gas drainage measure for coal seams with high coal‐gas outburst risk and low‐permeability, and it can simultaneously realize the functions of gas drainage before and during mining. Roadway tunneling has a strong influence on the stress and permeability properties of the adjusted coal seams, and further determines the gas drainage efficiency and the layout of the air‐return roadway. Taking the Pingshu Coal Mine as an example, this paper analyzes the influence of the vertical distance between the low‐level roadway and the underlying coal seam, and the influence of the width and height of the low‐level roadway on the stress relief and deformation characteristics. The results indicate that the low‐level roadway tunneling results in a nonuniform stress disturbance of coal seam #15. And a reasonable layout and size parameters of the air‐return roadway in coal seam #15 were proposed based on which gas drainage practices were carried out with good effects in panel #15211. The research can effectively guide the elimination of coal and gas outburst in return air roadway, and achieve the purpose of safe and rapid tunneling coal roadway under the environment of highly‐gassy coal seam. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.